This action might not be possible to undo. Are you sure you want to continue?

Welcome to Scribd! Start your free trial and access books, documents and more.Find out more

2, 130–137

**The Journal of Nonlinear Science and Applications
**

http://www.tjnsa.com

**PROOFS OF THREE OPEN INEQUALITIES WITH POWER-EXPONENTIAL FUNCTIONS
**

VASILE CIRTOAJE Dedicated to Themistocles M. Rassias on the occasion of his sixtieth birthday Communicated by Choonkil Park Abstract. The main aim of this paper is to give a complete proof to the open inequality with power-exponential functions aea + beb ≥ aeb + bea , which holds for all positive real numbers a and b. Notice that this inequality 1 1 was proved in [1] for only a ≥ b ≥ and ≥ a ≥ b. In addition, other two e e open inequalities with power-exponential functions are proved, and three new conjectures are presented.

1. Introduction We conjectured in [1] and [3] that e is the greatest possible value of a positive real number r such that the following inequality holds for all positive real numbers a and b: ara + brb ≥ arb + bra . (1.1) In addition, we proved in [1] the following results related to this inequality. Theorem A. If (1.1) holds for r = r0 > 0, then it holds for all 0 < r ≤ r0 . Theorem B. If max{a, b} ≥ 1, then (1.1) holds for any r > 0. Theorem C. If r > e, then (1.1) does not hold for all positive real numbers a and b.

Date : Received: August 19, 2010; Revised: November 24, 2010. c 2011 N.A.G. 2000 Mathematics Subject Classiﬁcation. Primary 26D10. Key words and phrases. Open inequality; Power-exponential function; AM-GM inequality.

130

Lemma 2.1) holds for all 0 < r ≤ e. A similar inequality is 2aa bb ≥ (ab)a + (ab)b . 1]. from Theorem B and its proof in [1]. The proof of Theorem 2. e then aea + beb ≥ aeb + bea . Notice that a proof of (2. b ∈ (0. If x ≥ 1 and 0 < y ≤ 1. 1]. b ∈ (0.4.1. c ∈ (0. we conjecture that the following sharper inequality still holds in the same conditions: Conjecture 2. then 1 − ln y ≥ e1−y .1. If a. Main result In order to give a complete answer to our problem. b. In the particular case r = 2.2) is given in [2]. namely the case 1 x where a = and b = . 1] and r ∈ (0. as follows. Notice that Lemma 2. r 2. 1] is the main case of the inequality (1. Lemma 2.1).3. (2. However. It seems that this inequality can be extended to three variables. If 0 < y ≤ 1. then √ 2 ara brb ≥ arb + bra . b ∈ (0. then 3aa bb cc ≥ (abc)a + (abc)b + (abc)c . Lemma 2. (2. Lemma 2. Conjecture 2. then (1.1 is a particular case of Theorem 2. If a and b are positive real numbers such that 0 < b ≤ ≤ a ≤ 1. If a.2. If x > 0. which is also an open problem. then xy−1 ≥ y x−1 . we only need to prove the following theorem.1) . 1 Theorem 2.1. e].2.1.1 relies on the following four lemmas. e e On the other hand. then ln x ≥ (x − 1)e1−x .2) where a.INEQUALITIES WITH POWER-EXPONENTIAL FUNCTIONS 131 1 Theorem D. If a and b are positive real numbers such that either a ≥ b ≥ or r 1 ≥ a ≥ b. If x ≥ 1. then xx − 1 ≥ (x − 1)ex−1 . we get the elegant inequality 2aa bb ≥ a2b + b2a . it follows that a.

Proof of Lemma 2. and hence f (y ) ≥ f (1) = 0. Since e1−x = 1 ex−1 ≤ 1 1 = . 1] and strictly increasing on [1. and then f (x) ≥ f (1) = 0. 1). f (y ) < 0 for 0 < y < 1. We have f (x) = y−1 − ln y ≥ y − 1 − ln y.2. Since g (y ) = 1 − ey−1 > 0 for 0 < y < 1. g (y ) ≤ g (1) = 0.4. where f (y ) = 1 − ln y − e1−y . we write the desired inequality as f (x) ≥ 0 for x ≥ 1. where f (x) = x ln x − ln[1 + (x − 1)ex−1 ] has the derivatives f (x) = 1 + ln x − and f (x) = xex−1 1 + (x − 1)ex−1 x(x − 1)ex−1 (ex−1 − 1) + (ex−1 − 1)2 . Therefore. Write the desired inequality as f (x) ≥ 0.3. where f (x) = ln x + This is true because f (x) = f (x) ≥ f (1) = 0. g (y ) is strictly increasing. where f (x) = (y − 1) ln x − (x − 1) ln y.132 V. and f (x) > 0 for x > 1. We need to show that f (y ) ≥ 0 for 0 < y ≤ 1.1. 1 + (x − 1) x 1 − 1. For ﬁxed y ∈ (0. x x−1 ≥ 0. and hence f (x) is strictly increasing for x > 0. f (y ) is strictly decreasing. x e1−y g (y ) . x[1 + (x − 1)ex−1 ]2 Since (x − 1)(ex−1 − 1) ≥ 0. Write the derivative in the form f (y ) = where g (y ) = y − ey−1 . Proof of Lemma 2. Proof of Lemma 2. CIRTOAJE 3. Since f (1) = 0. Proof of Lemmas Proof of Lemma 2. it follows that f (x) < 0 for 0 < x < 1. Consider the nontrivial case when 0 < y < 1. f (x) is strictly decreasing on (0. and hence x2 . ∞). f (x) is strictly increasing. we have f (x) ≥ 0. y it suﬃces to show that f (x) ≥ 0 for x ≥ 1.

By Lemma 2. it suﬃces to prove that g (y ) ≤ 0 for 0 < y ≤ 1. we have x y −1 yx − yxy + xy x−1 − y x ey−1 g (y ) ≤ (y − 1)xy−1 + x x−1 y −1 (x − y )(y −x ) = . Since g (1) = 0. Thus. and hence f (x) ≥ f (1) = 0. We have ey−1 g (y ) = (y − 1)xy−1 − yxy−1 ln x + (xy x−1 − y x )e1−x and.2. For ﬁxed x ∈ [1. For ﬁxed y ∈ (0. then f (x) ≥ f (1) = 0. and the conclusion follows. Since e1−x ≤ . g (y ) is strictly y decreasing on (0. then clearly g (y ) ≤ 0. If yxy−1 − yxy + xy x−1 − y x ≤ 0. by Lemma 2. Let us denote g (y ) = y − 1 − ln y . which is equivalent to x + y − 2 + (1 − y x )e1−x + (1 − xy )e1−y ≥ 0. we have xx ≥ 1 + (x − 1)ex−1 and y y ≥ 1 + (y − 1)ey−1 . Proof of Theorem 2. and then g (y ) > g (1) = 0. f (x) is strictly increasing for x ≥ 1. by Lemma 2. We have f (x) = 1 − e1−x − yxy−1 e1−y + y x (1 − ln y )e1−x and. (4. 1]. it suﬃces to show that (1 + (x − 1)ex−1 − y x )e−x + (1 + (y − 1)ey−1 − xy )e−y ≥ 0. x and.4. e]. 1). Therefore. let us denote g (y ) = 1 − e1−x − yxy−1 e1−y + y x e2−x−y .INEQUALITIES WITH POWER-EXPONENTIAL FUNCTIONS 133 1 < 0. f (x) > 0. Since g (y ) = 1 − 4. we get ey−1 g (y ) ≤ (y − 1)xy−1 + (yxy−1 − yxy + xy x−1 − y x )e1−x . we have to show that (xx − y x )e−x + (y y − xy )e−y ≥ 0 for 0 < y ≤ 1 ≤ x ≤ e.1) .3. 1 ≤ x ≤ e. We need to show that g (y ) ≥ 0.1. Consider now that 1 yxy−1 − yxy + xy x−1 − y x > 0. 0 < y ≤ 1. If f (x) ≥ 0. by Lemma 2. it follows that g (y ) ≤ 0. Therefore. where f (x) = x + y − 2 + (1 − y x )e1−x + (1 − xy )e1−y . the proof is completed.1 Making the substitutions x = ea and y = eb. it follows that f (x) ≥ 1 − e1−x − yxy−1 e1−y + y x e2−x−y . write this inequality as f (x) ≥ 0.

Other related inequalities We posted in [1] the following two open inequalities. and a proof of Proposition 5. Otherwise.1 Without loss of generality. Applying Lemma 6. If f (x) ≤ 0 for x ∈ [0.1. with equality for a = b = 1. We will give further a much simpler proof of Proposition 5. for a = 0 and b = 1. it suﬃces to show that f (x) ≤ 2.1. b are nonnegative real numbers satisfying a + b = 2. then k k a(2b) + b(2a) ≤ 1. the desired inequality is obvious.1. we rewrite the required inequality as g (x) ≥ 0. where f (x) = e3(1−x)(x− 2 + 3 ) + e−3(1+x)(x+ 2 + 3 ) .2. For a = 2 and b = 0.1 below. 0 ≤ x < 1. 2 A complicated solution of Proposition 5. . 2 f (x) ≤ 0 is equivalent to e−6x−5x ≥ 3 x2 x3 x2 x3 6 − 18x + 15x2 − 8x3 . then f (x) is decreasing. If a. 1 with equality for a = b = . Proposition 5.1 was given by L. Conjecture 5. and for a = 1 and b = 0. However.2 holds. assume that a ≥ b.2.134 V. then a2b + b2a ≤ 1. using the substitutions a = 1 + x and b = 1 − x. then a3b + b3a ≤ 2. Proposition 5. we can write the inequality as e3(1−x) ln(1+x) + e3(1+x) ln(1−x) ≤ 2. If k ≥ 1. it seems that the following generalization of Proposition 5. and hence f (x) ≤ f (0) = 2. b be nonnegative real numbers satisfying a + b = 1. 6 + 18x + 15x2 + 8x3 For the nontrivial case 6 − 18x +15x2 − 8x3 > 0. If a. b are nonnegative real numbers satisfying a + b = 1. where g (x) = −6x − 5x3 − ln(6 − 18x + 15x2 − 8x3 ) + ln(6 + 18x + 15x2 + 8x3 ). Matejicka in [4]. Let a. Proof of Proposition 5. 1). 6. CIRTOAJE 5. Since 9x2 5x3 15 4 f (x) =(3 − 9x + x2 − 4x3 )e3x− 2 + 2 −x 2 9x2 5x3 15 2 4 −(3 + 9x + x + 4x3 )e−3x− 2 − 2 −x .

applying Lemma 7.2) (7. which is equivalent to b2a ≤ 4ab2 + 2ab(a − b) ln a. we get b2a−1 ≤ 4a(1 − a) + 2a(2a − 1) ln(2a + b − 1). Similarly. 1). If t > −1. it suﬃces to show that (3 + 4x2 )(6 + 15x2 ) − 5x(18x + 8x3 ) ≥ (2 + 5x2 )(9 − 36x2 ).1 below for c = 2b. which is equivalent to a2b ≤ 1 − 4ab2 − 2ab(a − b) ln a. Since (6 + 15x2 )2 − (18x + 8x3 )2 ≤ (6 + 15x2 )2 − 324x2 − 288x4 ≤ 4(9 − 36x2 ).1) . 2 Applying Lemma 7. Proof of Proposition 5. Lemma 6.1. Therefore.2). f (t) = 7. the desired inequality follows. We need to prove that f (t) ≥ 0. d ≥ 0. (7. 0 ≤ c ≤ 1. ∞). f (t) ≥ f (0) = 0. we get a2b ≤ (1 − 2b)2 + 4ab(1 − b) − 2ab(1 − 2b) ln a. 2 3 Proof.2 for d = 2a − 1. 0] and increasing on [0. t+1 f (t) is decreasing on (−1. This reduces to 6x2 + 200x4 ≥ 0. then t2 t3 + . which is clearly true. 3 6 + 15x2 − (18x + 8x3 ) 6 + 15x2 + (18x + 8x3 ) it follows that g (x) ≥ 0 is equivalent to 2(6 + 8x2 )(6 + 15x2 ) − 20x(18x + 8x3 ) ≥ (2 + 5x2 )[(6 + 15x2 )2 − (18x + 8x3 )2 ]. assume that 1 0 ≤ b ≤ ≤ a ≤ 1. and hence g (x) ≥ g (0) = 0.2 Without loss of generality. Adding up (7. From 1 (6 + 8x2 ) − 10x (6 + 8x2 ) + 10x g (x) = −2 − 5x2 + + . 2 3 t3 .1) and (7. then g (x) is increasing. where ln(1 + t) ≤ t − f (t) = t − Since t2 t3 + − ln(1 + t).INEQUALITIES WITH POWER-EXPONENTIAL FUNCTIONS 135 If g (x) ≥ 0 for x ∈ [0.

d = 1. Since f (x) = f (x) is increasing. Using the substitution b = e−x − d. where f (x) = (1 − c)2 ex + c(2 − c) + c(1 − c)x − e(1−c)x . If 0 ≤ b ≤ 1 and d ≥ 0. Proof. f (x) = (1 − c)[(1 − c)ex + c − e(1−c)x ]. by the weighted AM-GM inequality. For 0 ≤ c ≤ 1. In order to prove this. too. we need to prove that f (x) ≥ 0. (1 + d) ln(1 + d) ≥ d. Proof. and for b = 0. −d . and for c = 1. To complete the proof. where f (x) = ln(1 + d) + ln(1 − d − dx) + dx − d ln(1 − dex ). For c ≥ 1. (1 − d − dx)(1 − dex ) . we need to prove that f (x) ≥ 0. we consider two cases. from 1 − d + d ln(b + d) ≥ 1 − d + d ln d ≥ 0. then bd ≤ 1 − d2 + d(1 + d) ln(b + d). and f (x) ≥ f (0) = 0. with equality for d = 0. and hence f (x) ≥ f (− ln(1 + d)) = ln[1 − d2 + d(1 + d) ln(1 + d)]. and hence f (x) ≥ 0. then f (x) is increasing. for c = 0. we get 1 − d + d ln(b + d) > 0. we have (1 − c)ex + c ≥ e(1−c)x . Excepting the equality cases. So. with equality for a = 1. by the weighted AM-GM inequality. that is. If f (x) ≥ 0 for x ≥ 0.1. If 0 < a ≤ 1 and c ≥ 0.136 V. we only need to show that −d2 + d(1 + d) ln(1 + d) ≥ 0. we may write the required inequality as ln(1 + d) + ln[1 − d + d ln(b + d)] ≥ d ln b. Lemma 7.2. we have (c − 1)ex + e(1−c)x ≥ c. Using the substitution a = e−x . − ln(1 + d) ≤ x ≤ − ln d. and hence f (x) ≥ 0. This inequality follows from ex ≥ 1 + x for x = 1+d d2 (ex − 1 − x) ≥ 0. x ≥ 0. then ac ≤ (1 − c)2 + ac(2 − c) − ac(1 − c) ln a. CIRTOAJE Lemma 7.

Nov.de/journals/JIPAM/article 1077. Matejicka. com/Forum/viewtopic. 2 3. J.php?t=118722]. 1. Solution of one conjecture on inequalities with power-exponential functions. [http://www. Art of Problem Solving Forum. Art. 5 2. 10 (1) (2009). 2006. Ineq.. Cirtoaje and A. (document). E-mail address : vcirtoaje@upg-ploiesti. Art.. 21. Zeikii.php?t=327116]. V.html?sid=1128]. V.de/journals/JIPAM/article1128. L.com/Forum/viewtopic. 5 * Department of Automatic Control and Computers.artofproblemsolving. 1. Pure Appl.ro . Art of Problem Solving Forum. [http:// www.artofproblemsolving.html?sid=1077]. 2010. Pure Appl. 10 (3) (2009). Romania. Cirtoaje. 2. Cirtoaje. [http://www. 72. J. Jan.INEQUALITIES WITH POWER-EXPONENTIAL FUNCTIONS 137 References 1. On some inequalities with power-exponential functions. University of Ploiesti. emis. V. Math. Math.emis. [http://www. 1 4. Ineq.

- Developing Intelligent Synthetic Logs Application to Upper Devonian Units in PA.pdf
- Reservoircharacterizationofa Permian.pdf
- Dynamic 3D reconstruction of deformable surfaces with stereo.pdf
- A Basin-Scale Shared Earth Model for Prospecting to Drilling and Beyond.pdf
- Developing Intelligent Synthetic Logs Application to Upper Devonian Units in PA.pdf
- A Study of the seismic noise from its long range correlation properties.pdf
- Case Histories of an Electromagnetic Method for Petroleum Exploration.pdf
- Case Histories of an Electromagnetic Method for Petroleum Exploration.pdf
- The Structure of the Core-Mantle Boundary From Diffracted Waves.pdf
- mathematics - mathematics of magic - a study in probability, statistics, strategy and game theory_x[1].pdf
- Methodological Solipsism Considered as a Research Strategy in Cognitive Psychology.pdf
- MATH History DUREN A century of mathematics in America Part I A1.pdf
- MATH Algebra MILNE Lie algebras - Algebraic groups - Lie groups.pdf
- MATH Logic HALVORSON Meta-logic derivation rules.pdf
- MATH Logic HALVORSON Review of the art of logic.pdf
- IPMCourseAgenda.pdf
- MATH Analysis REF.pdf
- BOOK GEOMETRY PROBLEM Proofs of Three Open Inequalities With Power Exponential Functions
- Book Geometry Problem Open Inequalities With Power Exponential Functions Conjecture4 6
- Book Geometry Problem New Rich Text Document
- Book Geometry Problem Slides
- Book Geometry Problem Open Inequalities With Power Exponential Functions Conjecture4 6
- Book Geometry Problem New Rich Text Document
- TECH Petroleum Petroleum Production System Analysis _ Viscosity Formulas

- The Disk and Shell Method
- Calc 1
- 103 Midterm
- Sequences
- Limits and Continuity
- Akki Rolles theorem
- 02_03
- Integration Substitution
- Integral
- Who Invented Calculus
- Yang X - Approximations for Constant e and Their Applications - J. Math. Anal. & Appl. 262 (2001) 651-659
- Limits
- Rudin
- Beyond Mere Convergence
- note1_UM101.pdf
- 131A Exam1 Sol
- THE AVERAGE OF THE ERDOS FUNCTION
- The Smarandache adjacent number sequences and its asymptotic property
- MIB.LECTURE6
- CALCULUS DIFFERENTIAL
- Fuzzy-3
- Ex2 Solution
- AP Calculus Notebook
- logical sequence of statment.txt
- My Homrwork Ms 2
- Limit Fails
- 1452-86300702335S
- Category Theory (Stanford Encyclopedia of Philosophy)
- Taylor Series
- Antiderivatives

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

We've moved you to where you read on your other device.

Get the full title to continue

Get the full title to continue listening from where you left off, or restart the preview.

scribd